The limits of ethics in international relations : natural law, natural rights, and human rights in transition - Boucher, David, 1951- (Oxford University Press, 2009)
Ethical constraints on relations among individuals within and between societies have always reflected or invoked a higher authority than the caprices of human will. For over two thousand years Natural Law and Natural Rights were the constellations of ideas and presuppositions that fulfilled this role in the west, and exhibited far greater similarities than most commentators want to admit. Such ideas were the lens through which Europeans evaluated the rest of the world. In his majornew book David Boucher rejects the view that Natural Rights constituted a secularisation of Natural Law ideas by s.